2015
DOI: 10.1159/000381061
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Somatostatin Receptors 1-5 and Dopamine Receptor 2 in Lung Carcinoids: Implications for a Therapeutic Role

Abstract: Objective: The expression of somatostatin receptors (SSTRs) and dopamine receptor 2 (DR2) in neuroendocrine tumors is of clinical importance as somatostatin analogues and dopamine agonists can be used for their localization and/or treatment. The objective of this study is to examine the expression of the five SSTR subtypes and DR2 in lung carcinoids (LCs). Methods: We conducted a retrospective study of 119 LCs from 106 patients [typical carcinoids (TCs): n = 100, and atypical carcinoids (ACs): n = 19]. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 40 publications
1
37
1
Order By: Relevance
“…The siNET cell line KRJ-I demonstrated equal mRNA expression levels for SSTR1 and SSTR2 [3]. In most studies where the quantitative mRNA expression levels of SSTRs were studied, SSTR2 was more highly expressed than SSTR1 [40,41,42,43,44]. In general, there is a predominant expression of SSTR1 and SSTR2 mRNA in NETs, with highly variable mRNA expression levels [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…The siNET cell line KRJ-I demonstrated equal mRNA expression levels for SSTR1 and SSTR2 [3]. In most studies where the quantitative mRNA expression levels of SSTRs were studied, SSTR2 was more highly expressed than SSTR1 [40,41,42,43,44]. In general, there is a predominant expression of SSTR1 and SSTR2 mRNA in NETs, with highly variable mRNA expression levels [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue specimens from the included patients had previously been subjected to IHC staining using the following primary antibodies: polyclonal rabbit SSTR1–5 (SSTR1:SS-840; SSTR2A:SS-800; SSTR3:SS-850; SSTR4:SS-880; SSTR5:SS-890; Gramsch Laboratories, Schwabhausen, Germany) polyclonal rabbit DR2 (Novus Biologicals, Littleton, CO, USA), novel monoclonal rabbit anti-SSTR2A, UMB-1 (Epitomics Inc, Burlingame, CA, USA); polyclonal rabbit OR51E1 (LSBio, Seattle, WA, USA); polyclonal goat IGF-1 (C-20), sc-7144 (Santa Cruz Biotechnology, Inc.); polyclonal rabbit IGF-1 Receptor beta (C-20), sc-713 (Santa Cruz Biotechnology, Inc.); polyclonal goat CTGF (L-20), sc-14939 (Santa Cruz Biotechnology, Inc.) and mouse monoclonal HIF-1 alpha ESEE 122, NB100–131 (Novus Biologicals, Burlingame, CA, USA), as previously described in this patient cohort [11-13]. …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the localization of receptor expression was assessed semi-quantitatively based on the classification by Volante et al [19] as follows: Score 1 (S1): pure cytoplasmic immunoreactivity; score 2 (S2): a minority tumour cell population showed membranous immunoreactivity in < 50% of the cell circumference, and score 3 (S3): a majority tumour cell population revealed membranous immunoreactivity in over 50% of the circumference [11, 12, 19]. The intensity of IHC staining for the IGF-1, IGF -1R, CTGF and HIF-1 antibodies were rendered only quantitatively with a 50% cut-off [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of currently available long-acting somatostatin analogues (octreotide or lanreotide) aims at reducing the secretion of vasoactive peptides from the carcinoid tumor, leading to symptomatic relief and a decrease in urine levels of 5-HIAA, as well as stabilization of the tumor size in up to half of patients [12,13,14]. Aggressive treatment in order to decrease 5-HIAA below 300 mmol/24 h is advisable, as more recent studies have shown that following the prolonged use of somatostatin analogues the incidence of CHD substantially decreases from 50 to 20-25% [15].…”
Section: Chd Treatmentmentioning
confidence: 99%